Metabolism of Klebsiella pneumoniae freeze-dried cultures for the design of BOD bioassays - Bonetto, Maria Celina (2012)
Aims: The survival rate of freeze-dried cultures is not enough information for technological applications of micro-organisms. There could be serious metabolic/structural damage in the survivors, leading to a delay time that can jeopardize the design of a rapid biochemical oxygen demand (BOD) metabolicbased bioassay. Therefore, we will study the metabolic activity (as ferricyanide reduction activity) and the survival rate (as colony-forming units, CFU) of different Klebsiella pneumoniae freeze-dried cultures looking for stable metabolic conditions after 35 days of storage. Method and Results: Here, we tried several simple freeze-drying processes of Kl. pneumoniae. Electrochemical measurements of ferrocyanide and survival rates obtained with the different freeze-dried cultures were used to choose the best freeze-drying process that leads to a rapid metabolic-based bioassay. Conclusions: The use of milk plus monosodium glutamate was the best choice to obtain a Kl. pneumoniae freeze-dried culture with metabolic stable conditions after storage at )20°C without the need of vacuum storage and ready to use after 20 min of rehydration. We also demonstrate that the viability and the metabolic activity are not always directly correlated. Significance and Impact of the Study: This study shows that the use of this Kl. pneumoniae freeze-dried culture is appropriate for the design of a rapid BOD bioassay. © 2012 The Authors. © 2012 The Society for Applied Microbiology.